Potential and Characteristics of Visitors to Lego-Lego South Sulawesi Tourism Objects in the Center Point of Indonesia (CPI) Makassar City - Nasruddin, Nur Amaliyah; Amiluddin, Amiluddin; Tahang, Hamzah; Arief, Andi Adri; Amri, Andi (PONGGAWA : Journal of Fisheries Socio-Economic, 2023)
This study aims to identify the potential, and determine the characteristics of visitors to the Lego Lego tourist attraction in South Sulawesi. The research was carried out in December 2021 - January 2022 at Lego Lego Sulsel Makassar City. The sample of this study consisted of a sample of tourists, tourist attraction managers, business people and fishermen at TPI Rajawali. Determination of tourist respondents using the Accidental Sampling technique with a total sample of 96 respondents. The data sources used are primary data and secondary data and then analyzed using descriptive analysis and frequency statistics. From the results of the study, it was found that the Lego Lego South Sulawesi tourist attraction has enormous potential in terms of attractiveness, accessibility, additional facilities and services available at the tourist attraction, as well as the potential from the economic aspect in terms of employment for the people affected by the reclamation. The characteristics of tourists are based on age, domicile, gender, occupation, average income, latest education, marital status, sources of information, purpose of visiting, intensity of visit, time of visit, visiting partners, transportation, costs and length of trip.